The effect of snowball strategy on the scientific sense and future thinking of sixth-graders in elementary science - Mahdi Younis, Wasf; Aziz jardo, hazim (Journal of College of Education, 2021)
The research aims to identify: (The effect of snowball strategy on the scientific sense and future thinking of sixth-graders in elementary science). To verify the two objectives of the research, the researchers developed two hypotheses: The researchers used the experimental design with two equal groups (an experimental group and a control group), and the research sample consisted of (78) pupils from the sixth grade elementary school in the Model School for Boys, which is located in Al-Zahraa neighborhood on the left side of the city of Mosul - Iraq, and after excluding the students The repeaters from the sample reached (68) students, by (36) students in Division (A) and (32) students in Division (B) .Accordingly, Division (A) will represent the control group, while (B) will be the experimental group, to suit The number of students to teach snowball strategy. The researchers used the following statistical methods: Statistical packages system for educational and psychological sciences, spss, Coder Richardson equation - 21., Effect size equation. Based on the results of the research, the researchers came up with several conclusions, the most important of which are: 1- The effectiveness of the snowball strategy and its preference over the usual way in the scientific sense and future thinking of sixth graders because it creates an atmosphere of familiarity and cooperation among them. 2 - The possibility of teaching this strategy in teaching science because it emphasizes the discovery of information and verification of its validity, not imposing it on it. 3- Students have increased their desire to learn science, which makes it an easy process for information and knowledge and their diversity, which makes teaching science a fun and effective lesson. The researchers recommended the following: 1- Resorting to the dependence of primary school teachers in their teaching on modern educational materials in general and snowball strategy in particular. 2- Holding intensive development courses by university teachers in the ministries of higher education and education for male and female teachers in primary schools to teach according to modern strategies and focus on effective teaching. 3-Focusing on making the student the center of the educational work by focusing on his ability to discover and develop his general scientific information and under the guidance and guidance of teachers only.